Pressure evolution in shallow magma chambers upon buoyancy‐driven replenishment. (24th March 2017) - Papale, P.; Montagna, C. P.; Longo, A.
Abstract: The invasion of active magma chambers by primitive magma of deeper provenance is a frequent occurrence in volcanic systems, and it is commonly associated with pressurization. Chamber replenishment is driven by pressure and buoyancy forces that cause magma ascent towards shallow depths. We examine the end‐member case of pure buoyancy‐driven (natural) convection in crustal reservoirs deriving from the presence of degassed, dense magma at shallow level, that can originate a gravitational instability. Space‐time‐dependent numerical simulations of magma dynamics in composite underground systems reveal highly nonlinear pressure evolution dominated by decompression at shallow depths. This counterintuitive result originates from the compressible nature of multiphase magmas and their complex convection and mixing dynamics. Shallow magma chamber decompression on replenishment is favored by large volatile contents of the uprising magma, resulting in large density contrasts among the resident and the incoming components. These results show that the intuitive concept of magma chamber pressurization upon replenishment may not always hold in real situations dominated by buoyancy, and provide new perspectives for the interpretation of geophysical records at active volcanoes. Plain Language Summary: A common process at active volcanoes worldwide is the arrival of magma from depth of tens of kilometers into shallower (depths of some km) reservoirs ("magma chambers"), containing themselves magma that can be different in terms of gas content and composition. We present numerical simulations that describe this process, with particular reference to the Campi Flegrei volcano in Italy. Our results show that, depending on the specific conditions and the gas contents of the two magma types, this process can lead to a decrease in pressure of the shallow chamber. When interpreting ground deformation signals, very often magma rise toward shallow depths is linked to inflation, caused by pressure increase. Our work suggests that this interpretation might sometimes be misleading or oversimplified. Key Points: Simulations of buoyancy‐driven magma chamber replenishment reveal heterogeneous pressure patterns Pressure in shallow magmatic reservoirs can decrease upon arrival of gas‐rich magma from depth The interpretation of ground deformation signals may be less simple than commonly thought